COVID-19: An overview of the current pharmacological interventions, vac‐ cines, and clinical trials (2020)
COVID-19, the greatest public health emergency of the 21st century, has affected 215 countries and territories around the world resulting in 15,151,738 confirmed cases and 621,121 deaths. The outbreak has continued at breakneck pace despite stringent public health measures, ravaging the global economy and causing profound human casualties. Vaccination is currently the best bet for the prevention of COVID-19. Still, in its absence, there has been considerable interest in repurposing existing therapeutic agents to reduce the severity of the illness and ease the burden on the already strained healthcare systems. This review outlines the current evidence regarding proposed treatments- experimental or repurposed, for COVID-19, and gives an insight into the clinical trial landscape for drugs as well as vaccines.